Peran Humas Pengadilan Negeri Surabaya dalam Memanfaatkan Media Sosial Instagram - Bunayya Hidayat, Rifki (Prodi Ilmu Komunikasi Universitas Sahid Surakarta, 2023)
The district court has a role in enforcing the law and providing information about legal services through Instagram social media. This study aims to explain the role of public relations at the Surabaya district court in utilizing Instagram social media. This research belongs to qualitative descriptive research. The data collection method includes documentation, namely screenshots of Instagram posts and interviews with public relations staff at the Surabaya district court. Respondents were selected based on predetermined criteria. The results of this study indicate that the public relations of the Surabaya district court have roles, namely: (1) communicator; (2) relationships; (3) backup management; and (4) corporate image. The research concluded that the public relations of the Surabaya district court were successful in carrying out its role by utilizing social media.